Improving Financial Management in Islamic Boarding Schools: Socialization of Accounting Guidelines and Financial System Application Tutorial - Sutrisno, catur Ragil; Ilmiani, Amalia; Al Farisi, Salman; Kushemanto, Andi; Prasetya, Nanda Agung; Khoiri, Habib (Community Development Journal, 2025)
Islamic boarding schools play a vital role in Indonesia's educational and social landscape. However, many of these institutions continue to face challenges in ensuring transparent and accountable financial management. Most rely on manual and basic record-keeping methods, lacking adherence to established accounting guidelines and the support of effective financial applications to streamline financial reporting and documentation. To address these issues, a Community Service (PkM) initiative was conducted to introduce Islamic boarding school accounting guidelines and provide hands-on assistance in using the Technology-Based Santri and Cooperative Financial System (Siskesakti) application. This initiative aimed to enhance participants' understanding and skills in financial management, ensuring compliance with accounting principles while integrating digital tools for financial administration. The program employed counseling and Participant Active Learning methods, allowing participants to engage actively in the learning process. The participants included financial administrators and teachers from partner Islamic boarding schools, including the Nurul Huda Banin Banat Islamic Boarding School, along with several other beneficiary institutions. The results of the program demonstrated a significant improvement in participants' comprehension of systematic financial management and their readiness to implement digital financial tools. With this assistance, partner Islamic boarding schools are expected to adopt a more structured, transparent, and accountable financial system, thereby supporting the institution’s long-term sustainability and financial integrity.